Peningkatan Hasil Belajar Kognitif Siswa Menggunakan Model Pembelajaran Kooperatif Tipe Group Investigation - Pertiwi, Dian Esti; Samsuri, Taufik; Muliadi, Agus (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2019)
[Title: Improving Student Cognitive Learning Outcomes using Cooperative Learning Model Type Group Investigation]. The purpose of this study was to improve student cognitive learning outcomes using the Cooperative Learning Model Type Group Investigation in class X MIA 2 students of SMAS NW Mataram in the 2018/2019 academic year. The subjects of this study were 15 students of class X MIA 2. This research is a classroom action research (CAR) consisting of two cycles. Observation sheet of learning implementation is used for each meeting to find out the implementation of learning steps according to the learning implementation plan observed by 2 observers. Test instruments of 20 multiple choice questions and 5 description questions were used in this study to find out the improvement of students' cognitive learning outcomes in each cycle. The results showed the implementation of learning in the cycle I (1) the first meeting reached 63.63% with a good category and the second meeting reached 88.8% with a very good category, (2) the cognitive learning outcomes of students in cycle 1 obtained an average value 59 with the classical completeness value achieved 46% of the incomplete category, while in cycle II (3) the first meeting of the implementation of learning reached 72.72% with a good category (4) the second meeting reached 94.44% with a very good category, and for results cognitive learning students obtained an average value of 72 with a classical completeness value achieved 76%. Based on the results of the study it can be concluded that the Cooperative Learning Model Type Group Investigation can improve cognitive learning outcomes of class X MIA 2 students of SMAS NW Mataram in the 2018/2019 academic year.